Bacteriological, Molecular, and Biochemical Evaluation of Seminal Fluid from Men with Primary Infertility Attending Federal Medical Centre, Bida, Niger State - Stephen Omanawo Anawo; Muhammed Abdullahi; Christian Ebere Nwachukwu; Ojogbane Matthew Abutu; Safiya Mohammed; Ojonimi Timothy Omede (West African Journal of Allied Health Sciences, 2026)
Introduction: Male infertility is a multifactorial condition in which microbial infections of the seminal fluid play a significant role. Both cultivable and fastidious organisms have been implicated in altering semen parameters, thereby compromising fertility potential. This study aimed to investigate the microbial profile, molecular detection of seminal pathogens, and their association with seminal fluid parameters and biomarkers among men with primary infertility attending the Federal Medical Centre (FMC) Bida, Niger State. Methods: A total of 207 semen samples from men with primary infertility were analyzed using standard bacteriological techniques and multiplex real-time PCR for microbial detection. Seminal biomarkers (fructose and zinc) were quantified and correlated with semen quality. Data were analyzed using descriptive statistics, Chi-square, and correlation coefficients, with significance set at p < 0.05. Results: Staphylococcus aureus (40.1%) and Escherichia coli (17.4%) were the predominant cultivable isolates, while molecular assays detected Ureaplasma parvum (9.7%), Ureaplasma urealyticum (9.2%), Gardnerella vaginalis (7.7%), Chlamydia trachomatis (7.2%), and Mycoplasma genitalium (6.8%) as major fastidious organisms. Abnormal semen parameters were significantly associated with microbial infections, including asthenozoospermia (54.1%, p = 0.005), teratozoospermia (54.6%, p = 0.043), and azoospermia (23.2%, p = 0.055). Elevated leukocyte counts were also observed (46.4%, p = 0.023). Biomarker analysis revealed elevated fructose in oligospermic and asthenozoospermic men (r = 0.994, p = 0.002; r = –0.733, p = 0.001), while zinc deficiency correlated significantly with reduced sperm motility and concentration (r = 0.817, p = 0.001). Conclusion: Seminal fluid infections, particularly by both cultivable and molecularly detected pathogens, significantly impair semen quality and are major contributors to primary infertility.